2020
DOI: 10.1007/s00405-020-05920-0
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic application of triamcinolone in sudden hearing loss—radiologic anatomy in cone beam CT and its’ correlation to clinical outcome

Abstract: Purpose To evaluate temporal bone cone-beam CT in patients with idiopathic sudden sensorineural hearing loss (ISSNHL) being treated with primary and secondary intratympanic (IT) triamcinolone and to possibly correlate these results to the clinical outcome. Methods Retrospective analysis of patients treated with IT triamcinolone for ISSNHL at our department in 2018. Pre-and post-therapeutic audiologic examinations included four-tone average (FTA) at 0.5, 1, 2 and 3 kHz. Using a clinical questionnaire, pre-thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Other studies in the literature have described the anatomic landmarks of the RW to guide cochlear implantation procedures. 9 Roßberg et al, 10 in their retrospective study of conebeam CT examinations in 27 patients before treatment with intratympanic steroids, found granulation tissue obscuring the RWN in 15% (4/27) of patients, similar to our results with a larger cohort. Schachern et al 11 found histologic evidence of granulation tissue in the RWN following experimentally induced otitis media in a cat model.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies in the literature have described the anatomic landmarks of the RW to guide cochlear implantation procedures. 9 Roßberg et al, 10 in their retrospective study of conebeam CT examinations in 27 patients before treatment with intratympanic steroids, found granulation tissue obscuring the RWN in 15% (4/27) of patients, similar to our results with a larger cohort. Schachern et al 11 found histologic evidence of granulation tissue in the RWN following experimentally induced otitis media in a cat model.…”
Section: Discussionsupporting
confidence: 90%
“…Silverstein found out in an examination of 41 RWNs via tympanostomy and middle ear endoscopy that five were completely obstructed and seven were partially obstructed [ 21 ]. However, even after overcoming anatomic obstructions in the middle ear, problems with round window permeability for compounds, the loss of medications into the nasopharynx via the Eustachian tube, and drug pharmacokinetics within inner ear fluids can still vary significantly [ 12 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…How can we evaluate RWNV by noninvasive measurement? Previous inner ear imaging studies mostly focused on the measurement of the round window niche (RWN) and its position relationship with adjacent structures (such as the cochlear basal turn and facial nerve) to assess its impact on cochlear implantation, [18][19][20][21][22][23][24][25] but little attention had been paid to the existence of RWNV and its possible clinical effects.…”
Section: Introductionmentioning
confidence: 99%